THE CORRELATION OF LONG-TERM COMBINATION TREATMENT OF VALPROIC ACID AND TOPIRAMATE ON SERUM VITAMIN D LEVELS AMONG CHILDREN WITH EPILEPSY - Hexanto Muhartomo; M.I Widiastuti; Endang Kustiowati; Aris Catur Bintoro; Arinta Puspita Wati; Alifiani Hikmah Putranti; Rony Parlindungan Sinaga (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Epilepsy is a chronic condition characterized by unprovoked seizure. Vitamin D is necessary in child development process and is strongly influenced by the presence of anti-epileptic drugs.Objective: To determine the correlation of treatment duration and serum vitamin D levels in children with epilepsy who use the combination of valproic acid and topiramateMethods: A cross sectional study among forty pediatric patients with epilepsy with age range of 5-10 years at Dr. Kariadi Hospital Semarang. Examination of serum vitamin D levels is done by ELISA. Statistical analysis using Spearman correlation test and partial correlation test with significance level p = 0.05.Results: The mean of serum vitamin D levels in patient with combination treatment after 24 months was 21.87±1.21ng/ml, in those who still having seizure was 27.94±2.40ng/ml, and among who received delayed therapy was 23.23±2.07ng/ml. Bivariate analysis depicted that there was negative correlation between duration of treatment (rho= -0.850, p<0.001), onset of therapy (rho=0.604, p<0.001) and seizure frequency (rho=0.559, p<0.001) with serum vitamin D levels. Partial correlation analysis showed a significant correlation between duration of treatment and serum vitamin D levels after adjusted by onset of therapy (rho=-0.839, p<0.001) and seizure frequency (rho=-0.856, p<0.001).Conclusion: There is a correlation between the duration of treatment and serum vitamin D levels among children with epilepsy